Deal breakers : when to work on a relationship and when to walk away - Marshall, Bethany (Simon Spotlight Entertainment, 2007)
Relationships are hard work, but how hard should they be? When do you know you are struggling too hard? This is a book about emotionally unhealthy men--the ones who make you question, "Is it him or is it me? I tell him how I feel, but he says I'm overreacting or needy or it's all my fault." This book is about getting out of "relationship purgatory," where the present is unfulfilling and the future is the only thing you can hope for--but there is no magic future. In business, a deal breaker is the nonnegotiable term that, if not agreed to, means the deal is off. But in relationships, identifying your deal breaker can be more promising, as it holds out the possibility of helping you to understand where the relationship has gone wrong, what needs to be done to make it better, and when to walk away.--From publisher description.